2022
DOI: 10.3389/fonc.2022.939790
|View full text |Cite
|
Sign up to set email alerts
|

Microarray and bioinformatic analysis reveal the parental genes of m6A modified circRNAs as novel prognostic signatures in colorectal cancer

Abstract: BackgroundAccumulating evidences have revealed that the abnormal N6-methyladenosine (m6A) modification is closely associated with the occurrence, development, progression and prognosis of cancer. It is noteworthy that m6A modification is widely existed in circRNAs and found its key biological functions in regulating circRNAs metabolism. However, the role of m6A modified circRNAs in colorectal cancer (CRC) remains unknown. To better understand the role of circRNAs in the pathogenesis of CRC, we focus on the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A previous study reported that Gab1 overexpression in DLD-1 colon carcinoma cells promoted tumor growth in a subcutaneous model ( 71 ), which is consistent with the in vitro findings from Bai et al ( 72 ). In contrast, Liang et al delineated the tumor-suppressing role for Gab1 in CRC ( 73 ). In our study, we generated mice with Gab1 -KO in normal intestinal epithelium, followed by AOM/DSS induction to mimic the progression of inflammation-associated carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that Gab1 overexpression in DLD-1 colon carcinoma cells promoted tumor growth in a subcutaneous model ( 71 ), which is consistent with the in vitro findings from Bai et al ( 72 ). In contrast, Liang et al delineated the tumor-suppressing role for Gab1 in CRC ( 73 ). In our study, we generated mice with Gab1 -KO in normal intestinal epithelium, followed by AOM/DSS induction to mimic the progression of inflammation-associated carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, computational methods are developed based on the MeRIP-seq data to map m 6 A modifications in circRNA [ 151 , 152 ]. In addition, due to its unique property of low total RNA input, m 6 A-circRNA epitranscriptomic microarray [ 153 , 154 ] is coming into vogue. However, microarray based on the hybridization of probes must have the sequence of the samples in advance.…”
Section: Identification Of M 6 a Modification In C...mentioning
confidence: 99%